ПИТАННЯ РОЗРОБЛЕННЯ МОДЕЛЕЙ СИСТЕМНОЇ АВТОМАТИКИ ДЛЯ ДОСЛІДЖЕННЯ АВАРІЙНИХ РЕЖИМІВ ЕЛЕКТРОЕНЕРГЕТИЧНИХ СИСТЕМ - Буткевич, О.Ф.; Гурєєва, Т.М.; Юнєєва , Н.Т. (Інститут електродинаміки Національної академії наук України, 2024)
The peculiarities of the approach used for the development of digital models of system automation devices to power systems fault condition simulation are considered. Some issues related to the practical development of digital models of system automation devices of power systems are briefly outlined. The role of the graphical interface as a tool for preparing such models and manipulating them is shown. Using the examples of automatic frequency unloading and automatic elimination of asynchronous modes, the features of the functioning and setting up of the models are analyzed. The results of the use of the developed models during the Interconected power system of Ukraine fault condition simulation are presented. Ref. 3, fig. 8.